PENGUATAN KAPASITAS BENGKEL KONVERSI UNTUK MENDUKUNG PROGRAM KENDARAAN RAMAH LINGKUNGAN - Mufti Reza Aulia Putra; Nizam, Muhammad; Adriyanto, Feri; Inayati, Inayati; Warindi, Warindi; Slamet Saputro, Joko; Anwar, Miftahul; Ramelan, Agus; Magfiroh, Hari; Brilianto Apribowo, Chico Hermanu (CV. Kalimasada Group, 2025)
The capacity strengthening program for electric vehicle conversion workshops at SMK Karya Nugraha Boyolali was implemented through a synergistic collaboration model between universities, vocational schools, and industry. This study employed a qualitative descriptive approach with a case study method to evaluate the effectiveness of the six-month program. The findings revealed a significant improvement in participants’ technical competencies, as evidenced by the increase in pre-test and post-test scores, as well as the successful development of a solar photovoltaic (PV)-based electric vehicle charging station prototype. Beyond technical achievements, the program also strengthened multi-stakeholder collaboration and fostered the creation of a micro-scale clean energy ecosystem within the school environment. These results demonstrate that practice-based vocational training combined with strategic collaboration can make a substantial contribution to achieving the Sustainable Development Goals (SDGs), particularly clean energy (SDG 7), industry innovation (SDG 9), and climate change mitigation (SDG 13).